RECOGNIZING THE CREATIVE INDUSTRY POTENTIAL OF TIDUNG ISLAND IN KEPULAUAN SERIBU, DKI JAKARTA AS A TOURISM DESTINATION - Siti Gomo Attas; Gres Grasia Azmin; Marwiah Marwiah (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
The purpose of this study is to identify the potential of the creative industry in Tidung Island, Kepulauan Seribu, DKI Jakarta as a tourism destination. The existence of Tidung Island as a tourism destination on a populated island gives its own character to the existence of an island that has the potential to be used as a creative industry. The existing potential of Tidung Island such as cultural tourism and nature tourism would certainly be better if all stakeholders, namely the local government such as the regent, the Department of Tourism and Creative Industries, the Department of Culture, sub-district head, village head, and the community collaborated with each other in elevating the potential of Tidung Island as a tourist destination. . The method in this research uses ethnographic methods with observation, interviews and documents. The theory used in this study uses the theory of local wisdom, creative industries, and cultural commodification. The results of this study explore the potential of cultural tourism as the character of the people of Tidung Island and the potential of marine tourism as an icon of Tidung Island in particular and Pulau Seribu in general to represent tourist destinations as the right choice supported by a creative industry that can benefit the people of Tidung Island specifically and Pulau Seribu in DKI Jakarta.